Quercetin against Emerging RNA Viral Diseases: Potential and Challenges for Translation - Subudhi, Bharat B.; Swain, Ranjit Prasad (Current Molecular Medicine, 2023)
Due to higher adaptability and mutability, there is always a possibility for RNA viral disease outbreaks. There are no approved antivirals for the majority of RNA viruses, including SARS-CoV-2, CHIKV, DENV, JEV, ZIKV, and EBOV. To treat these infections and prepare for future epidemics, it is necessary to identify effective therapeutic strategies with broad-spectrum actions against RNA viruses. Unregulated inflammation is the major cause of the severity associated with these viral diseases. Quercetin is a privileged molecule that is known to interfere at different levels of inflammatory response. Besides, it modulates pathways responsible for viral translation as well as the immune response of the host. It has also been found to inhibit replication by targeting critical targets of some of these viruses. Due to its abilities to inhibit viral targets, modulate host factors or a combination of both, quercetin has been demonstrated to help recover from some of these viral diseases in preclinical /clinical studies. Thus, it can be a drug candidate for application against a broad range of viral diseases. However, its translational value is limited by the lack of large-scale clinical studies. A major hurdle for oral application is poor solubility. Thus, developing a suitable form of quercetin can enable adequate bioavailability, leading to its translational application.
Keywords: RNA virus